(untitled) (IITM Journal of Business Studies, 2025)
This paper addresses the critical imperative for banking institutions, particularly in India, to cultivate enduring relationships with customers with a focus on Customer Relationship Management (CRM) and its effect on service quality satisfaction and customer loyalty. The research employs Partial Least Square Structural Equation Modeling (PLS-SEM) to analyze the relationship between CRM perception and customer loyalty with customer satisfaction from service quality acting as a mediator. The findings reveal significant positive path coefficients, affirming that a positive perception of CRM practices influences customer satisfaction from service quality as well as customer loyalty. Additionally, the research establishes a significant and positive impact of customer satisfaction on customer loyalty, and identifies a complementary partial mediation effect suggesting that customer satisfaction from service quality mediates between CRM perception and customer loyalty relationship. These findings provide a robust framework for understanding the dynamics shaping customer-bank relationship, allowing banking firms to strategically enhance customer satisfaction and loyalty. The study emphasizes the ongoing need for banks to adapt and refine their CRM practices to align with the evolving needs of customers, ultimately adding value to all stakeholders involved in the financial landscape.